Pengaruh Model Problem Based Learning (PBL) terhadap Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar - Sari, Hilda; Zainil, Melva; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at finding out the effects of applying the problem based learning model toward students’ skill in solving mathematics problems at Class V of SDN 05 Surau Gadang, Padang. This quantitative research used the quasi experiment method. The population was all 5th grade students of the school. The sample was chosen using the saturation and random sampling techniques. Two classes were drawn to be experimental and control classes. From the draw, it was got that Class VB as the experimental class and Class VA as the control one. The research result shows that the score of t-test with a significant level of 0,05 was tcount (2,228) > ttable (2,001). Thus, H1 is accepted while H0 is denied. Keywords: PBL, Skill in Solving Mathematics Problems